CONSTRUCTIVE AND TECHNOLOGICAL CONSIDERATIONS ON HEAT TRANSFER OPTIMIZATIONS FOR BATTERY CELL WITH PARALLELEPIPED HEAT SINKS (Nonconventional Technologies Review, 2023)
The paper deals with the analysis of heat dissipation in batteries for electric and hybrid vehicles. In addition to the part of creating the model for simulating the thermal flow, the way in which the excess heat is taken over by the cooling system of the space where the battery is positioned is also considered. It should also be noted that in the final part of the work, a solution for the realization of the cooling system through additive manufacturing is proposed to ensure, on the one hand, a better heat dissipation, but also the realization of such a system with much lower manufacturing costs lower than the costs involved at this time in a ventilation cooling system or with a copper or aluminium pipe.
Keywords: deposit materials; additive manufacturing; diffuse liver disorders; heat transfer; modelling materials